Organomodification of San Nicolas clay using sodium-soybean oil surfactant - Labarez, Kelvin Hans L.; Peabody, Steven Joseph C.; Garcia, Vincent Joseph (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The rubber industry in the Philippines is at a disadvantage in part due to having to import fillers for reinforcing rubber to achieve proper mechanical properties. One common rubber filler is modified kaolin clay, which must be modified to maximize its effectiveness. An alternative to this is modified montmorillonite clay, which is easier to process. Large deposits of bentonite clay, mainly composed of montmorillonite and other similar clays, can be found in the country, making it enticing as a substitute. Raw bentonite clay from San Nicolas, Ilocos Norte was physically and chemically purified before being modified with a sodium-soybean oil surfactant. X-ray diffraction showed negligible change of d-spacing. Fourier-transform infrared spectroscopy showed the presence of bonds indicating that the surfactant was present in modified samples. Scanning electron microscopy did not show observable platelet formation; instead, indicating the clay did not delaminate, implying the proposed modification method caused surfactant to attach itself only to the surface and edges. Larger amounts of surfactant and longer mixing time are recommended.
Thesis (B.S. Materials Engineering)--University of the Philippines Diliman
Keywords: Bentonite; Clay minerals